WEBSITE SEKOLAH UNTUK MENUNJANG PENERIMAAN PESERTA DIDIK BARU DI SMP MUHAMMADIYAH 10 SURAKARTA - Heru Supriyono; Reza Benarivo; Muamaroh Muamaroh (WARTA LPM, 2019)
One of the main problems faced by SMP Muhammadiyah 10 Surakarta is how to attract new students to register. Manual promotion based on leaflets and brochures currently used by the school is among the root of problems that make school only recognized by the society around the school in the restricted geographical area. Another obstacle for the community is the manual registration process for new students, which require the prospective student to come to the school. In this publication, internet technology was proposed to solve these two problems. The objectives of the community services are to widen the promotional scope of SMP Muhammadiyah 10 Surakarta and to enable the prospective student to register online via the school website. The activities of the community services are involving purchasing a web domain for school standard, hosting the website, training for administrator, and evaluation from the society. The results of the community services include school website, and the teacher has been trained as an administrator. Assessment from the society results showed that 74.68% of respondents provided positive feedback that the site is satisfying and beneficial.Keywords: PPDB online, school, website